Graphene-based Ni/TiO2 nanocomposite electrode material for sustainable hydrogen evolution reaction - Pradnya G. Kedar; Anup Kumar Pradhan; Asmita S. Jadhav; Chanchal Chakraborty; Sopan T. Ingle (Results in Surfaces and Interfaces)
Electrochemical water splitting is an attractive, green, and renewable energy method for hydrogen production due to the abundance of water resources, zero pollution, and high purity. An efficient, stable, and low-cost electrocatalyst is essential for production of pure and clean hydrogen. A straightforward and economical method to synthesize electrocatalysts for efficient hydrogen evolution reaction (HER) is crucial for its practical application. Herein, we have synthesized and reported the application of Nickel-Titania over Graphene (Gr@Ni/TiO2) nanocomposite which is reasonably efficient and highly durable. The catalyst (Gr@Ni/TiO2) 0.2 and 0.4 M ratios were synthesized with the simple co-precipitation method. The standard three-electrode system is used to carry out the HER activity in 1M KOH solution. Due to high conductivity and specific surface area, the synthesized Gr@Ni/TiO2 catalyst (0.4M) achieves low overpotential 101 mV at a current density of 20 mA cm−2. With such electrocatalytic performance and environment friendliness, the Gr@Ni/TiO2 holds significant promise toward efficient hydrogen production.